Complexity-reduction by first-order approximation of non-linear kinetics - Michael Becka (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1998)
Ecological, toxicological, and pharmacological research is often concerned with the answer to the question of how a substance is processed within a biological system. The exact knowledge of the corresponding kinetic pattern forms the basis for a useful answer. In order to identify non-linear kinetics, a first-order approximation method is proposed for complexity-reduction. A simulation study is presented to investigate the error of the approximation in case of a simple Michaelis-Menten kinetic process. The proposed method shows to give useful results which allow to characterize the underlying kinetic pattern. Furthermore it could be shown that in simulating kinetic processes the applied numerical methods may perform with considerable numerical instabilities.
Keywords: 519; Compartmental model; Dynamic process; First-order approximation; Michaelis-Menten kinetic; Non-linear kinetic; Numerical integration